OSCE best practice guidelines—applicability for nursing simulations. Issue 1 (January 2016) - Kelly, Michelle; Mitchell, Marion; Henderson, Amanda; Jeffrey, Carol; Groves, Michele; Nulty, Duncan; Glover, Pauline; Knight, Sabina
Abstract Background Objective structured clinical examinations (OSCEs) have been used for many years within healthcare programmes as a measure of students' and clinicians' clinical performance. OSCEs are a form of simulation and are often summative but may be formative. This educational approach requires robust design based on sound pedagogy to assure practice and assessment of holistic nursing care. As part of a project testing seven OSCE best practice guidelines (BPGs) across three sites, the BPGs were applied to an existing simulation activity. The aim of this study was to determine the applicability and value of the OSCE BPGs in an existing formative simulation. Methods A mixed methods approach was used to address the research question: in what ways do OSCE BPGs align with simulations. The BPGs were aligned and compared with all aspects of an existing simulation activity offered to first-year nursing students at a large city-based university, prior to their first clinical placement in an Australian healthcare setting. Survey questions, comprised of Likert scales and free-text responses, used at other sites were slightly modified for reference to simulation. Students' opinions about the refined simulation activity were collected via electronic survey immediately following the simulation and from focus groups. Template analysis, using the BPGs as existing or a priori thematic codes, enabled interpretation and illumination of the data from both sources. Results Few changes were made to the existing simulation plan and format. Students' responses from surveys (n  = 367) and four focus groups indicated that all seven BPGs were applicable for simulations in guiding their learning, particularly in the affective domain, and assisting their perceived needs in preparing for upcoming clinical practice. Discussion Similarities were found in the intent of simulation and OSCEs informed by the BPGs to enable feedback to students about holistic practice across affective, cognitive and psychomotor domains. The similarities in this study are consistent with findings from exploring the applicability of the BPGs for OSCEs in other nursing education settings, contexts, universities and jurisdictions. The BPGs also aligned with other frameworks and standards often used to develop and deliver simulations. Conclusions Findings from this study provide further evidence of the applicability of the seven OSCE BPGs to inform the development and delivery of, in this context, simulation activities for nurses. The manner in which simulation is offered to large cohorts requires further consideration to meet students' needs in rehearsing the registered nurse role.